2008
DOI: 10.4088/pcc.v10n0404
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Rivastigmine in Patients With Alzheimer's Disease Not Responding Adequately to Donepezil

Abstract: Immediately switching patients from donepezil to rivastigmine without a washout period was safe and well tolerated in the current study. Additionally, these results suggest that patients not responding adequately to or declining while taking donepezil may improve or stabilize after switching to rivastigmine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…After excluding 4,324 papers after title and abstract review, 264 full‐text articles were examined, and 31 studies were \ included in the systematic review with meta‐analysis (22 longitudinal studies without a control group; 9 cohort studies with a control group) (Supplementary Figure S1). Seven of those were open‐label studies . The 22 longitudinal studies included a total of 34 independent cohorts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After excluding 4,324 papers after title and abstract review, 264 full‐text articles were examined, and 31 studies were \ included in the systematic review with meta‐analysis (22 longitudinal studies without a control group; 9 cohort studies with a control group) (Supplementary Figure S1). Seven of those were open‐label studies . The 22 longitudinal studies included a total of 34 independent cohorts.…”
Section: Resultsmentioning
confidence: 99%
“…Seven of those were open-label studies. [20][21][22][23][24]33,37 The 22 longitudinal studies included a total of 34 independent cohorts.…”
Section: Resultsmentioning
confidence: 99%
“…This study, conducted from October 2003 to January 2005, was a 26-week open-label extension of a prospective, 26-week, open-label, single-arm, multicenter study conducted in the United States, the design and results of which have been reported in detail elsewhere. 13 In brief, eligible patients commenced treatment during the core phase with rivastigmine 1.5 mg b.i.d., and the time between the last dose of donepezil and the first dose of rivastigmine was not to have exceeded 7 days. If the patient tolerated the starting dose, the dose could be increased to 3 mg b.i.d.…”
Section: Methodsmentioning
confidence: 99%
“…8,10 It may, therefore, be beneficial to switch between ChEIs if patients fail to respond to treatment, deteriorate, or are unable to tolerate their current treatment. 11,12 A recent 26-week open-label study 13 showed that switching patients immediately (i.e., without a washout period) to rivastigmine 3 to 12 mg/day after poor response to donepezil improved or stabilized global functioning in almost 70% of patients. The immediate switch was also safe and well tolerated.…”
mentioning
confidence: 99%
“…In another, 26-week open-label study (N=270), patients with mild-to-moderate AD not responding to donepezil were switched to receive rivastigmine 3-12 mg/day. Improvement/stabilization of AD was reported in 69.7% of patients (136/195, observed case analysis) who did not respond to the treatment or declined while taking donepezil and were immediately switched from donepezil to rivastigmine [ 43 ].…”
Section: Switching Between Cheismentioning
confidence: 99%